PREFERENSI DAN PERILAKU MASYARAKAT PEDESAAN TERHADAP PERBANKAN SYARIAH (Studi Kasus Di Desa Luwunggede, Mundu Dan Karangreja) - Muhammad Abdul Aziz; Lutfia Nuril Arafah (Universitas Darussalam Gontor, 2021)
Since the issuance of the 2003 MUI fatwa about the interest is forbidden, Islamic banks are growing rapidly but its slower than conventional banks market share. The villager has not been reached to socialize about the activities of Islamic banks. So as the villager who have low income levels, related only to conventional financial institutions such as cooperatives, rural banks, banks and even moneylenders because the Islamic financial institutions are not reached by them. This study aims to analyze religious and economic preferences and behaviour of rural people towards Islamic banking. This study uses descriptive statistical analysis research with quantitative and qualitative approaches. The data used are primary and secondary data obtained from questionnaires distributed to 90 respondents and interviews from certain figures. The data analysis method used is frequencies.The results of the study show that religious and economic preferences are the most important factors that greatly influence to the behavior of rural people towards Islamic banking.This makes Islamic bank is urgent to accommodate that can not be done by conventional bank, especially in terms of the maslahah afterlife in order to stay away from usury that is unlawful so it is in line with the Islamic principal مَا لَا يُدْرَكُ كُلُّهُ لَا يُتْرَكُ كَلُّهُ and الْمَيْسُوْرُ لَايَسْقُطُ بِالْمَعْسُوْرِ.